Financial management compliance of the income generating projects (IGP) of the Bicol University College of Agriculture and Forestry (BUCAF) with the IGP Operating manual - Redoblado, Rey Joseph; Abellanosa, Darlygie; Asis, Skala Marie; Morin, Beverly (2016)
Practice of financial management is essential to the operation, sustainability, and growth of an enterprise. This study focuses on the practices of income-generating projects of Bicol University's College of Agriculture and Forestry. Moderate compliance was noted because of conflict of functions and lack of knowledge of key persons in areas of budgeting and financial reporting. The respondents accepted that the standards set by the manual helped in their operations. Recommendations are trainings in financial reporting for the personnel and enhancement of the manual.
Keywords: Financial management